2015
DOI: 10.1136/postgradmedj-2014-132672
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent miscarriage: causes, evaluation and management

Abstract: Recurrent miscarriage is frustrating for the physician and a heartbreaking experience for the patient. Approximately 5% of couples trying to conceive have two consecutive miscarriages. Despite a thorough study of patients, the aetiology of this common obstetric complication is unknown in 50% of cases. Known causes include abnormal chromosomes, endocrinological disorders and uterine abnormalities. Although antiphospholipid antibodies have been demonstrated in miscarriages, the role played by alloimmune mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
145
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(158 citation statements)
references
References 92 publications
4
145
0
9
Order By: Relevance
“…Although the cause of most miscarriages is unknown, they presumably result from a complex interplay between parental age, genetic, hormonal, immunological, and environmental factors 910. Genetic factors, including parental chromosomal rearrangements and abnormal embryonic genotypes or karyotypes, could underlie more than half of recurrent miscarriages 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cause of most miscarriages is unknown, they presumably result from a complex interplay between parental age, genetic, hormonal, immunological, and environmental factors 910. Genetic factors, including parental chromosomal rearrangements and abnormal embryonic genotypes or karyotypes, could underlie more than half of recurrent miscarriages 10.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors, including parental chromosomal rearrangements and abnormal embryonic genotypes or karyotypes, could underlie more than half of recurrent miscarriages 10. Maternal age is the strongest known risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…Antiphospholipid syndrome is the most important acquired risk factor for a treatable cause of recurrent pregnancy loss and can be found in 5–15% of cases (33). RM is part of APS clinical classification criteria (34, 35) that include vascular thrombosis and pregnancy morbidity.…”
Section: Aps Tai and Pregnancymentioning
confidence: 99%
“…2 Recurrent pregnancy loss (RPL), in contrast, is considered as a distinct clinical entity. 3,4 The commonly accepted RPL risk factors include cytogenetic abnormalities, endocrine abnormalities, anatomical factors, immunological factors, inherited thrombophilia, infectious disease, malefactors, and miscellaneous factors such as psychological, lifestyle, environmental, and occupational factors. 1 Later on, according to the criteria set by the American Society for Reproductive Medicine (ASRM), 2 RPL was re-defined as two or more consecutive miscarriages excluding molar, ectopic, and biochemical pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, RPL was defined as a disorder of three or more consecutive pregnancy failures prior to 20th gestational week, and it only affected 1% of couples aiming to conceive. [1][2][3][4][5] Several lines of evidence have shown that the presence of autoimmune diseases as well as their associated autoantibodies increased the risk of pregnancy loss. Approximately 5% of women are estimated to suffer RPL.…”
Section: Introductionmentioning
confidence: 99%